The Mitochondrial Na+/Ca2+ Exchanger Inhibitor CGP37157 Preserves Muscle Structure and Function to Increase Lifespan and Healthspan in Caenorhabditis elegans - García-Casas, Paloma; Alvarez-Illera, Pilar; Gómez-Orte, Eva; Cabello, Juan; Fonteriz, Rosalba I.; Montero, Mayte; Alvarez, Javier (Frontiers in Pharmacology, 2021)
We have reported recently that the mitochondrial Na+/Ca2+ exchanger inhibitor CGP37157 extends lifespan in Caenorhabditis elegans by a mechanism involving mitochondria, the TOR pathway and the insulin/IGF1 pathway. Here we show that CGP37157 significantly improved the evolution with age of the sarcomeric regular structure, delaying development of sarcopenia in C. elegans body wall muscle and increasing the average and maximum speed of the worms. Similarly, CGP37157 favoured the maintenance of a regular mitochondrial structure during aging. We have also investigated further the mechanism of the effect of CGP37157 by studying its effect in mutants of aak-1;aak-2/AMP-activated kinase, sir-2.1/sirtuin, rsks-1/S6 kinase and daf-16/FOXO. We found that this compound was still effective increasing lifespan in all these mutants, indicating that these pathways are not involved in the effect. We have then monitored pharynx cytosolic and mitochondrial Ca2+ signalling and our results suggest that CGP37157 is probably inhibiting not only the mitochondrial Na+/Ca2+ exchanger, but also Ca2+ entry through the plasma membrane. Finally, a transcriptomic study detected that CGP37157 induced changes in lipid metabolism enzymes and a four-fold increase in the expression of ncx-6, one of the C. elegans mitochondrial Na+/Ca2+ exchangers. In summary, CGP37157 increases both lifespan and healthspan by a mechanism involving changes in cytosolic and mitochondrial Ca2+ homeostasis. Thus, Ca2+ signalling could be a promising target to act on aging.